Perancangan Sistem Informasi Stok Obat Klien Berbasis Web Pada Pusat Rehabilitas Narkoba Ar Rahman - Kms Muhammad Revaldi; Fenny Purwani (CV. ITTC INDONESIA, 2024)
Currently the use of technology in the dissemination of information is very important for organizations or agencies. An information system is currently very supportive of activities for organizations or agencies which will then be processed again to be more useful for users of the information system itself. The Ar-Rahman Drug Rehabilitation Center itself is a rehabilitation center for drug addicts. to support their work, the staff at the Ar Rahman Drug Rehabilitation Center are currently using the facilities available there. One of them records the client's drug stock. At present the problems found at the Ar Rahman Narcotics rehabilitation center are: recording is still done manually, namely by recording which items must be recorded in stock. From these reasons, it is very necessary to build a Client Drug Stock Information System Design at the Ar Rahman Drug Rehabilitation Center which functions to record what assets are already owned which were previously recorded manually in the future to be digital. In the design it will use dfd and erd while the database uses waterfall. The expected results are a client drug stock system design that will be implemented in . Ar-Rahman Drug Rehabilitation Center and can be used as a basis for developers to create a drug stock system. Ar-Rahman Drug Rehabilitation Center.